Penerapan Metode Snowballa Throwing dalam Meningkatkan Kualitas Belajar Siswa pada Mata Pelajaran PAI - Fattahul Falah; Siskha Putri Sayekti; Abdi Prayudi; Ahmad Fikri Baydhowy (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This study applies the Snowball Throwing method to improve the quality of student learning in PAI subjects. This study used the Classroom Action Research (PTK) approach in two cycles at SDI Daruttaqwa schools. Data was collected through classroom observation, PAI teacher interviews, and assessment of learning outcomes. The results showed that the application of the Snowball Throwing method consistently improved the quality of student learning and their motivation in PAI learning. These findings provide practical implications for PAI teachers in improving learning and contributing to the use of snowball trhowing methods in learning. Improving the quality of student learning is the main goal of education. Various methods and strategies have been developed to increase the effectiveness of learning. One approach that has proven effective is the application of Snowball Throwing in learning. The concept of Snowball Trhowing is similar to a snowball being thrown. In a learning context, students begin by asking questions or sharing ideas relevant to the topic being studied. Then, they threw the question or idea to other classmates. Classmates then give new responses or thoughts related to the question or idea. The results of this study showed an increase in the quality of student learning, namely in cycle I by 57.14%, then in cycle II it increased to 94.28%. This translates to an increase of 37.14%. Thus, the use of the Snowball Trhowing learning method is able to improve the quality of student learning.